Pengalaman Pasien Terdiagnosa Kanker Paru Ditinjau dari Teori Elisabeth Kubler-Ross - Murhayeni Murhayeni; Rika Sabri; Dally Rahman (Journal of Telenursing (JOTING), 2023)
This study aims to look at the patient's experience when diagnosed with lung cancer through the theoretical perspective of Elisabeth Kubler-Ross. The research method used is p qualitative with a phenomenological approach. The results of this study show several themes, one of which is the support needed by patients when diagnosed with lung cancer. Participants have sources of help, namely personal ability, family support, and the support of the Health Team, especially nurses. In conclusion, when someone is experiencing a bad condition caused by a disease, what is needed is support from all parties around them who can provide reinforcement and motivation to patients when diagnosed with lung cancer so that they get a strong foundation that becomes the main factor influencing participants in undergoing disease treatment. Keywords: Elisabeth Kubler-Ross, Lung Cancer, Experience